How makerspaces can support learning across disciplines - Jaryal, Kiran Kumari (Trinity College (Dublin, Ireland). School of Education, 2022)
In this systematic literature review, various papers on makerspaces in education, and their impact across disciplines were studied. This study is more focused on the senior school settings and children of related age groups but some part also talks about outside school settings as well. This research is based on a qualitative and quantitative methodology. Also, the materials used in makerspaces projects have been taken into consideration including robotics kits E.g. – Arduino, Lego, VEX, etc. to find out how the use of the material in makerspaces can affect student’s learning in various disciplines. Background – The maker movement (explained in detail in the introduction section of the paper) had a huge impact on the education world but - • how to incorporate it into student’s learning across disciplines – what kind of setup and modifications are needed in the traditional setup • how organically it will support the various studies done on child development such as – constructivism, pedology aspect, etc. • how it will be helping in understanding other subject concepts creatively and affect the design thinking of children to deal with real-world problems. • what could be the right material? The research would be incomplete if we do not talk about the above questions. In the study, the above aspects were also given a lot of importance and tried to find the answer to the above which leads to answering the big question of the research. Findings – During the study, the following were very evident - • Positive impact on students learning through project-based learning across disciplines not only Science, Technology, Engineering, and Math, but other subjects like English and Arts as well. Makerspaces activities connect with STEAM subjects organically • Knowledge and understanding are barriers to makerspaces use in schools and outside schools. • Scope of research toward the interdisciplinary aspect. • Student Led projects can be done effectively in the makerspaces with great learning outcomes. • Importance of makerspaces in developing engineering skills • Implementation and managing makerspace the material in makerspaces is a big challenge • Teacher Training is an Importance aspect as it is different from the traditional method of teaching and learning. • Choice of Materials – 3D printers, Robotics kits- VEX, Arduino, raspberry pi, and other supporting material plays a crucial role in innovations. • Entrepreneurship skills take shape in the makerspaces naturally. Conclusion – The research is concluded with recommendations and suggestions. It has been studied that there is an evident positive impact of makerspace on students learning but there is a lack of study behind the structured curriculum catering to the impact across disciplines. Some suggestions on the unit plans on various subjects have been given by the end of the study. It has been seen that there is a critical need for the development of hands-on projects which could connect to various subjects and a solid curriculum catering to real-world problems which could also be part of all subjects taught in school not only focused on STEAM.
Keywords: Science Education; Education